Online Media As a Learning Medium For Students to Improve English Speaking Skill In The Era of Digitalization - Fikni, Zahratul; Maysuroh, Siti; Taufik, M. Rama; Husnu, Muhammad (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2024)
This study looks into how YouTube can help people become more fluent in English speakers. The goal of this study was to generate thorough findings that could be utilized as a teaching tool to help educators, instructors, and students get better at speaking English. A speaking test was used as the research instrument, and the sample for this study consisted of 28 students in class VII from SMPN 4 Pringgabaya. Students took a pre-test and a post-test to gauge their proficiency speaking English; the pre-test was administered before they utilized YouTube as a learning tool, and the post-test was administered following their use of YouTube. Microsoft Excel was used for the statistical analysis of the data. According to study results, the N-gain score is 0.51—that is categorized as having a minimal impact on students' ability to speak English while utilizing YouTube as a learning tool.